METHODOLOGY FOR SCIENTIFICALLY BASED DETERMINATION OF FUEL CONSUMPTION FOR MILITARY TRUCKS USING THE EXAMPLE OF MAN TGM 13.320 IN THE SUBDIVISIONS OF THE NATIONAL GUARD OF UKRAINE - Putro, Oleksandr (Honor and Law, 2025)
The method for determining the fuel consumption of military trucks is considered using the example of MAN TGM 13.320 trucks operated by units of the National Guard of Ukraine. A computational and analytical approach is proposed that takes into account design parameters and specific operating conditions. A comparison of analytical and empirical data showed similar results (23.8 l/100 km and from 22.8 l/100 km to 26 l/100 km), confirming the reliability of the model. The optimal speed of 70 km/h with a minimum fuel consumption of 22.9 l/100 km was determined. It is noted that the results obtained can be used to standardize fuel consumption and improve the logistical support of the National Guard units.